PERFORMANCE MEASUREMENT USING HUMAN RESOURCE SCORECARD AT PT. JAYA FARM 7 - Stella Angelina; Nazaruddin; Yeni Absah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
Performance measurement that is not comprehensive will result in performance measurement that is not optimal, resulting in a lack of awareness in evaluating the performance of human resources. The performance measurement carried out by the company is still not optimal in determining the part of employee performance that needs to be evaluated with the aim that employee performance in the long term will achieve the company's targets. Performance measurement is carried out using the Human Resource Scorecard based on 4 perspectives, namely the Financial Perspective, Customer Perspective, Internal Business Process Perspective, and Learning and Growth Perspective. The measurement also uses the Analytical Hierarchy Process (AHP) 6 method to determine the weight of importance for each Key Performance Indicator (KPI). In the results of research using the Human Resource Scorecard, there are 10 strategic targets consisting of 2 strategic targets from a financial perspective, 2 strategic targets from a customer perspective, 4 strategic targets from a business process perspective and 2 strategic targets from a growth and learning perspective. The research results after weighting show that the financial perspective has the highest priority weight. Based on the strategic target of producing 10 KPIs, of which there are 5 KPIs that have not reached the company target consisting of production income levels, employee satisfaction, turnover rates, work accident rates and DOC depletion rates - and 5 KPIs that have reached the company targets consist of operational costs, meeting implementation. /evaluation, employees who meet the company's needs, employees' ability to innovate and the amount of employee training.